Peningkatan Kepemimpinan Karang Taruna RW 21 Desa Suci Manyar Gresik - Rahmat Agus Santoso (Jurnal Pengabdian Manajemen, 2021)
The purpose of this service is to carry out the Leadership learning process, and improve the quality of Team Effectiveness. Materials for the Styles of Leadership, and Effective Team program are given using lecture and discussion methods. The target audience is the administrators and coaches of Karang Taruna. The results of the Focus Group Discussion (FGD) showed that telling leadership could not increase the quantity of activities and the quality of activities as well as the time used. The leadership learning process at the Karang Taruna organization RW 21 Suci Village, Manyar District, Gresik Regency, the behavior of the leader succeeded in influencing his group members to carry out the work. Improving the quality of Team Effectiveness in the organization Karang Taruna RW 21 Suci Village, Manyar District, Gresik Regency, selling, participating, and delegating leadership can improve the performance of its members.